Democracy in the Shadow of Political Dynasties - Elly Warnisyah Harahap; Mhd. Syaikah Widya Syahr; Thorino Ivan Doloksaribu; Ummy Al-Fiqro Napitupulu; Naila Hadisty Ananta; Ahmad Afriza (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Democracy is a form of government in which all eligible citizens have equal rights in the decisions of their lives.The main principles of democracy include freedom, equality and justice.A democratic government provides a way for people to participate in freedom, equality, justice in politics, such as participating in elections, being given freedom of opinion and other things.Politics is an activity or process related to decision-making or regulation in a group or society. It involves the formation and implementation of public policy, the division of power, and the interaction between individuals, groups, and institutions.Political dynasty refers to a situation in which power is inherited from generation to generation in a particular family.The purpose of this research is to take Ahmad Ibn Hambal and Ibn Taymiyyah's thoughts on democracy in the shadow of political dynasties.This research uses quantitative methods with collection and uses literature studies. Democracy in the shadow of political dynasties can create a concentration of power and limit access and political opportunities for others in society.